CZE determination of submicromolar level of phenol in seawater using improved dynamic pH junction. Issue 19 (3rd August 2016) - Yasuno, Koki; Fukushi, Keiichi
Abstract : Using an improved dynamic pH junction as an on‐line concentration procedure, we developed CZE for determining submicromolar phenol in seawater for chloride to phenol concentration ratios of 1 000 000. To enhance the effect of conventional dynamic pH junction, a saturated fatty acid solution was injected into the capillary after sample injection. We named the procedure an improved dynamic pH junction. The method requires no sample pretreatment. The following optimum conditions were established: BGE, 40 mM sodium tetraborate decahydrate adjusted to pH 9.8 containing 0.001% m/v hexadimethrine bromide; 190 nm detection wavelength; 18 s (370 nL) vacuum injection period of sample; a saturated fatty acid solution, 30 mM sodium n ‐hexanoate; 20 s (420 nL) vacuum injection period of the sodium n ‐hexanoate; and 15 kV applied voltage with the sample inlet side as the cathode. The LOD for phenol was 5.9 μg/L at S/N of 3. The respective values of the RSD (intraday) of the peak area, peak height, and migration time for phenol were 1.9, 2.9, and 0.46%. The recoveries of phenol (25‒100 μg/L) spiked into the natural seawater sample obtained using the peak areas were 92‒110%. The proposed method was applied to simple biodegradation experiments using natural seawater samples containing phenol.